N-cadherin-mediated adhesion and signaling from development to disease: Lessons from mice - Radice, Glenn L. (Prog Mol Biol Transl Sci, 2013)
Of the twenty classical cadherin subtypes identified in mammals, the functions of the two initially identified family members E- (epithelial) and N- (neural) cadherin have been most extensively studied. E- and N-cadherin have mostly mutually exclusive expression patterns, with E-cadherin expressed primarily in epithelial cells whereas N-cadherin is found in a variety of cells, including neural, muscle and mesenchymal cells. N-cadherin function in particular appears to be cell-context-dependent, as it can mediate strong cell–cell adhesion in the heart, but induce changes in cell behavior in favor of a migratory phenotype in the context of epithelial–mesenchymal transition (EMT). The ability of tumor cells to alter their cadherin expression profile, e.g. E- to N-cadherin, is critical for malignant progression. Recent advances in mouse molecular genetics, and specifically tissue-specific knockout and knock-in alleles of N-cadherin, have provided some unexpected results. This chapter highlights some of the genetic studies that explored the complex role of N-cadherin in embryonic development and disease.